Relationship of explicit/implicit self‐esteem discrepancies, suicide ideation, and suicide risk in patients with major depressive disorder. Issue 6 (22nd August 2022) - Yin, Xunbao; Shen, Jianfei; Jiang, Nengzhi; Sun, Jing; Wang, Yanyu; Sun, Hongwei
Abstract: The present study was conducted to explore the associations between explicit self‐esteem (ESE), implicit self‐esteem (ISE), ESE/ISE discrepancies, depression severity, suicidal ideation (SI), and suicide risk among patients with major depressive disorder (MDD). To this end, 36 MDD patients with SI, 35 MDD patients without SI, and 32 healthy controls were recruited. All participants were interviewed using the Mini International Neuropsychiatric Interview (MINI), and they also completed the Beck Depression Inventory (BDI). The Beck Scale for Suicide Ideation‐Chinese Version (BSI‐CV) and the Rosenberg Self‐Esteem Scale (SES) were used for the analysis. Further, the Implicit Association Test (IAT) was conducted to assess participants' ISE. The study revealed significant differences in ESE among the three groups, F (2, 90) = 44.88, p  < .001. In particular, the group of MDD patients with SI had the lowest score. The interaction between the size and direction of ESE/ISE discrepancy was associated with depression severity, β = −.50, p  = .004, and SI, β = −.39, p  = .045. Among the four types of self‐esteem, individuals with diminished self‐esteem had the highest SI score whereas individuals with low congruent self‐esteem had the highest suicide risk score. Based on these findings, the study suggested that diminished self‐esteem could help in the early detection of depression and SI. Low‐congruent self‐esteem may also be considered a screening factor for suicide risk.